School's out: what are urban children doing? The Summer Activity Study of Somerville Youth (SASSY). - Tovar, Alison.; Lividini, Keith.; Economos, Christina D.; Folta, Sara.; Goldberg, Jeanne.; Must, Aviva. (2016)
Background: Research indicates that in the United States, children experience healthier BMI and fitness levels during school vs. summer, but research is limited. The primary goal of this pilot study was to assess where children spend their time during the months that school is not in session and to learn about the different types of activities they engage in within different care settings. A secondary goal of this pilot study was to learn what children eat during the summer months.; Springer Open.